Recurrent aspiration pneumonia after laparoscopic adjustable gastric banding for obesity surgery - Leena Jalota; Adetokunbo Oluwasanjo; Richard Alweis (Greater Baltimore Medical Center, 2014)
Laparoscopic adjustable gastric banding (LAGB) is an increasingly common therapeutic option in the management of obesity and certain obesity-related comorbid conditions. As it gains popularity for its advantages of being minimally invasive and reversible, clinicians should be aware of growing evidence of esophageal and pulmonary complications, which may be irreversible and associated with long-term morbidity. We report a case of esophageal and pulmonary complications in a patient with successful weight loss after lap-band surgery necessitating its removal.